Pulmonary infection and baseline mRS scores predict poor prognosis in anti-GABABR encephalitis - Ding, Junqing; Xu, Dingkang; Lv, Jie; Wu, Tianwen; Li, Jinghong; Tian, Mi; Lian, Yajun (Frontiers in Immunology, 2022)
Purpose: We aimed to explore factors affecting response to first-line treatments in patients with anti-gamma-aminobutyric-acid B receptor (anti-GABABR) encephalitis. Methods: Thirty-four patients with an initial diagnosis of anti-GABABR were enrolled retrospectively from December 2015 to June 2021. Clinical characteristics and experimental test data were collected from the patients’ medical records within 24 h of admission. The Modified Rankin Scale (mRS) was utilized to assess disease severity at admission and functional recovery after immunotherapy. Independent prognostic factors were determined by ordinal logistic regression analysis. Results: Of the total number of anti-GABABR encephalitis patients, 12 (12/34, 35%) presented with tumors, and all had lung cancer. According to multivariate regression analysis, the anti-GABABR encephalitis with tumor group showed a decreased peripheral blood absolute lymphocyte count (ALC) (OR: 0.063, 95% CI: 0.006-0.639, P=0.019) and hyponatremia (OR: 9.268, 95%CI: 1.054-81.502, 0.045). In addition, neutrophil/lymphocyte ratio (NLR), monocyte/lymphocyte ratio (MLR) and platelet-lymphocyte (PLR) did not differ significantly in mRS scores in patients with first-line treatments. Furthermore, no patients with mild-moderate mRS scores (0-2) on admission developed symptoms after treatment; only 11 patients with a severe mRS score (≧3, 11/18) experienced symptom alleviation. Ordinal regression analysis indicated an association between worse prognosis and pulmonary infection (OR=9.885, 95% CI: 1.106-88.323, P=0.040) and baseline mRS score (OR= 24.047, 95% CI: 3.294-175.739, P=0.002) in adjusted model. Conclusion: To our knowledge, this is the largest single-center study on anti-GABABR encephalitis. The findings demonstrate that pulmonary infection and baseline mRS are independent risk factors for poor prognosis in GABA encephalitis after first-line treatment. ALC and hyponatremia are potential biomarker for clinical evaluation of patients with anti-GABABR accompanied by lung cancer. Positive second-line immunotherapy should be considered.